Wakefields in a cluster plasma - Mayr, M. W.; Ceurvorst, L.; Kasim, M. F.; Sadler, J. D.; Spiers, B.; Glize, K.; Savin, A. F.; Bourgeois, N.; Keeble, F.; Ross, A. J.; Symes, D. R.; Aboushelbaya, R.; et al. (Physical Review Accelerators and Beams, 2019)
We report the first comprehensive study of large amplitude Langmuir waves in a plasma of nanometer-scale clusters. Using an oblique angle single-shot frequency domain holography diagnostic, the shape of these wakefields is captured for the first time. The wavefronts are observed to curve backwards, in contrast to the forwards curvature of wakefields in uniform plasma. Due to the expansion of the clusters, the first wakefield period is longer than those trailing it. The features of the data are well described by fully relativistic two-dimensional particle-in-cell simulations and by a quasianalytic solution for a one- dimensional, nonlinear wakefield in a cluster plasma.